The Wintertime Covariation of CO2 and Criteria Pollutants in an Urban Valley of the Western United States. Issue 5 (12th March 2018) - Bares, Ryan; Lin, John C.; Hoch, Sebastian W.; Baasandorj, Munkhbayar; Mendoza, Daniel L.; Fasoli, Ben; Mitchell, Logan; Catharine, Douglas; Stephens, Britton B.
Abstract: Numerous mountain valleys experience wintertime particulate pollution events, when persistent cold air pools (PCAPs) develop and inhibit atmospheric mixing, leading to the accumulation of pollutants. Here we examine the relationships between trace gases and criteria pollutants during winter in Utah's Salt Lake Valley, in an effort to better understand the roles of transport versus chemical processes during differing meteorological conditions as well as insights into how targeted reductions in greenhouse gases will impact local air quality in varying meteorological conditions. CO2 is a chemically inert gas that is coemitted during fossil fuel combustion with pollutants. Many of these coemitted pollutants are precursors that react chemically to form secondary particulate matter. Thus, CO2 can serve as a stable tracer and potentially help distinguish transport versus chemical influences on pollutants. During the winter of 2015–2016, we isolated enhancements in CO2 over baseline levels due to urban emissions ("CO2ex "). CO2ex was paired with similar excesses in other pollutant concentrations. These relationships were examined during different wintertime conditions and stages of pollution episodes: (a) Non‐PCAP, (b) beginning, and (c) latter stages of an episode. We found that CO2ex is a good indicator of the presence of gaseous criteria pollutants and a reasonable indicator of PM2.5 . Additionally, the relationships between CO2ex and criteria pollutants differ during different phases of PCAP events which provide insight into meteorological and transport processes. Lastly, we found a slight overestimation of CO:CO2 emission ratios and a considerable overestimation of NO x :CO2 by existing inventories for the Salt Lake Valley. Key Points: Elevated CO2 correlates with enhancements in several National Ambient Air Quality Standard criteria pollutants CO2 provides insight into meteorological, chemical, and transport processes during persistent cold air pool events Emission inventories overestimate CO:CO2 and NO x :CO2 ratios